Energy efficiency in China: The local bundling of interests and policies - Genia Kostka; William Hobbs (Frankfurt School of Finance & Management, 2010)
With the end of China's 11th Five-Year Plan approaching, this paper analyzes sub-national governments' implementation strategies to meet national energy efficiency targets. Previous research focuses on the way governance practices and decision-making structures shape implementation outcomes, yet very little attention has been given to what strategies local leaders actually employ to bridge national priorities with local interests. To illustrate how leaders work politically, this paper highlights specific implementation mechanisms officials use to strengthen formal incentives and create effective informal incentives to fulfill their energy efficiency mandates. The analysis is drawn from fifty-three interviews conducted in June and July 2010 in Shanxi, a major coal-producing and energy-intensive province. Findings suggest that local government leaders conform to the national directives by 'bundling' the energy efficiency policy with policies of more pressing local importance or by 'bundling' with the interests of groups with significant political influence. Ultimately, officials take national policies and then frame them in ways that give them legitimacy at the local level.
Keywords: D73; D78; O18; R58; Q48; Q58; 330; China; local state; policy implementation; energy policy; governance; Umweltverträgliche Energiepolitik; Energiesparen; Einführung; Kommunalpolitik; Public Choice; China